2019
DOI: 10.1098/rspb.2018.2332
|View full text |Cite
|
Sign up to set email alerts
|

New Caledonian crows infer the weight of objects from observing their movements in a breeze

Abstract: Humans use a variety of cues to infer an object's weight, including how easily objects can be moved. For example, if we observe an object being blown down the street by the wind, we can infer that it is light. Here, we tested whether New Caledonian crows make this type of inference. After training that only one type of object (either light or heavy) was rewarded when dropped into a food dispenser, birds observed pairs of novel objects (one light and one heavy) suspended from strings in front of an electric fan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…NC crows show evidence for the ability to transfer causal knowledge between perceptually distinct problems (Taylor et al 2007;, though it is not clear if this is via functional generalisation or true analogical reasoning. They also can mentally preplan solutions to problems and make inferences, such as reasoning by exclusion (Jelbert et al 2015a;2015b) and inferring the weight of novel objects from observing their movements in the wind (Jelbert et al 2019). There is also some evidence that NC crows might be capable of representing hidden causal mechanisms (Taylor et al 2012a;2012b; but see Boogert et al 2013;Dymond et al 2013;Taylor et al 2013a;, but there is currently no conclusive evidence that they form representations of unobservable ones (Neilands et al 2016;Taylor et al 2009), nor that these birds possess the ability to make causal interventions (Taylor et al 2014; but see Jacobs et al 2015;Taylor et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…NC crows show evidence for the ability to transfer causal knowledge between perceptually distinct problems (Taylor et al 2007;, though it is not clear if this is via functional generalisation or true analogical reasoning. They also can mentally preplan solutions to problems and make inferences, such as reasoning by exclusion (Jelbert et al 2015a;2015b) and inferring the weight of novel objects from observing their movements in the wind (Jelbert et al 2019). There is also some evidence that NC crows might be capable of representing hidden causal mechanisms (Taylor et al 2012a;2012b; but see Boogert et al 2013;Dymond et al 2013;Taylor et al 2013a;, but there is currently no conclusive evidence that they form representations of unobservable ones (Neilands et al 2016;Taylor et al 2009), nor that these birds possess the ability to make causal interventions (Taylor et al 2014; but see Jacobs et al 2015;Taylor et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Corvids shared a common ancestor with primates over 300 million years ago, but show comparable performance with primates in some cognitive tasks, including in some cases, with young children (Cheke et al 2012;Emery and Clayton 2004). New Caledonian crows routinely use tools in both foraging and non-foraging contexts, and have performed impressively across a wide range of problem-solving tasks (Gruber et al 2019;Hunt 1996;Jelbert et al 2015Jelbert et al , 2019Taylor et al 2012;von Bayern et al 2009). We assessed performance in crows and children using this automated paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Work on tool use in birds have produced a number of intriguing findings, suggesting that birds are capable of sophisticated technical intelligence ( Weir et al, 2002 ; Taylor et al, 2007 , 2010a ; Tebbich et al, 2007 ; Bird and Emery, 2009 ; von Bayern et al, 2009 , 2018 ; Wimpenny et al, 2009 ; Auersperg et al, 2010 , 2011b , 2012b ; Teschke and Tebbich, 2011 ; St Clair and Rutz, 2013 ; Laumer et al, 2016 ; Jelbert et al, 2018 , 2019 ; Fayet et al, 2020 ). While some of these studies suggested that birds might be capable of mental trial and error during tool use, conclusive evidence that birds can mentally represent tool problems only emerged recently, from a study on New Caledonian crows ( Gruber et al, 2019 ).…”
Section: Intelligent Behavior Beyond Pure Associationmentioning
confidence: 99%